Successful Treatment of Severe Metabolic Acidosis Due to Acute Aluminum Phosphide Poisoning With Peritoneal Dialysis: a Report of 2 Cases (Iranian Journal of Kidney Diseases, 2017)
Aluminum phosphide poisoning is common in our region. It can cause severe metabolic acidosis and persistent hypotension, which lead to cardiogenic shock and subsequently mortality. Oliguric or anuric acute kidney injury is seen in almost all patients with aluminum phosphide poisoning. Renal replacement therapies are recommended in these patients to improve metabolic acidosis and increase the rate of survival. We report 2 cases of severe acute aluminum phosphide poisoning treated successfully with peritoneal dialysis.